Environment-based Learning Media with Green Biochemistry Approach - Muhamad Iksan; Frida Maryati Yusuf; Dyah Pramesti Istana Ardiyati (Postgraduate, University of Mataram, 2023)
Southeast Sulawesi is one of the provinces that has the largest mining area in Indonesia. One of the main mining commodities is nickel, which has the largest natural resource potential of around 97.3 billion tons of nickel minerals. Mining has an important role in the development of a region because it produces industrial raw materials, a source of foreign exchange, employment and increases local revenue. On the other hand, mining can cause various threats or adverse impacts in the form of environmental damage and pollution. One of the areas experiencing adverse impacts from mining is Baliara Village, Bombana Regency. This study aims to determine the formulation of efforts to overcome and prevent seawater pollution by nickel waste using the green biochemistry approach. This research was conducted in April 2022 in Baliara Village, Bombana Regency using observation, interview and literature study approaches. The results showed that there are approaches that can be used to control or reduce nickel waste, namely using the flotation-filtration method, silica-modified tofu solid waste, utilization of mangrove vegetation as nickel heavy metal phytoremediation and the establishment of corporate social responsibility (CRS) by mining companies in controlling or monitoring environmental pollution. This approach is considered very effective in controlling pollution in the aquatic environment in Baliara Village, Bombana Regency, so that it can serve as scientific input and information for relevant parties in taking actions and policies in controlling pollution in the area